Rhamnogalacturonan-I enriched pectin from steamed ginseng ameliorates lipid metabolism in type 2 diabetic rats via gut microbiota and AMPK pathway. (30th January 2023) - Ren, Ting; Liu, Furao; Wang, Dongxue; Li, Bo; Jiang, Peng; Li, Junming; Li, Hui; Chen, Changbao; Wu, Wei; Jiao, Lili
Abstract: Ethnopharmacological relevance: Panax ginseng C. A. Meyer (Ginseng) has traditionally been used to treat diabetes. Polysaccharide is the main active component of ginseng, and has been proved to have hypoglycaemic and hypolipidaemic effects, but its mechanism remains unclear. Aim of the study: This study aimed to evaluate the effect and the potential mechanism of rhamnogalacturonan-I enriched pectin (GPS-1) from steamed ginseng on lipid metabolism in type 2 diabetes mellitus (T2DM) rats. Materials and methods: GPS-1 was prepared by water extraction, ion-exchange and gel chromatography. High-glucose/high-fat diet combined with streptozotocin was used to establish T2DM rat models, and lipid levels in serum and liver were tested. 16S rRNA sequencing and gas chromatography-mass spectrometry were used to detect the changes of gut microbiota and metabolites. The protein and mRNA levels of lipid synthesis-related genes were detected by Western blot and quantitative real-time polymerase chain reaction. Results: The polyphagia, polydipsia, weight loss, hyperglycaemia, hyperlipidaemia and hepatic lipid accumulation in T2DM rats were alleviated after GPS-1 intervention. GPS-1 modulated the gut microbiota composition of T2DM rats, increased the levels of short-chain fatty acids, and promoted the secretion of glucagon-like peptide-1 and peptide tyrosine tyrosine. Further, GPS-1 activated AMP-activated protein kinases, phosphorylated acetyl-CoA carboxylase, reduced the expression of sterol regulatory element-binding protein-1c and fatty acid synthases in T2DM rats. Conclusions: The regulation effects of GPS-1 on lipid metabolism in T2DM rats are related to the regulation of gut microbiota and activation of AMP-activated protein kinase pathway. Graphical abstract: Image 1 Highlights: A RG-I enriched pectin (GPS-1) was isolated from steamed ginseng. GPS-1 regulated gut microbiota structure and increased the level of metabolite SCFAs. SCFAs promoted GLP-1 secretion and then activated liver AMPK by ''gut-liver'' axis. GPS-1 improved lipid metabolism in T2DM rats via gut microbiota and AMPK pathway.